2010
DOI: 10.1159/000278713
|View full text |Cite
|
Sign up to set email alerts
|

An Aggressive Extramedullary Cutaneous Plasmacytoma Associated with Extreme Alterations in the Innate Immune System

Abstract: Background: The role of natural killer (NK) cells in plasma cell diseases has not yet been fully characterized. Case Report: We present the case of a 47-year-old man with an extremely aggressive extramedullary plasmacytoma of the lung with associated cutaneous lesions, whose disease was accompanied by a significantly decreased number of NK cells (CD56+, CD16+, CD3–) in the peripheral blood, very low NK cell activity levels, and a decreased interleukin-2 production from cultured cells in vitro. Histology and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…Also, the degree of NK impairment was correlated with the clinical severity of the disease and the response to therapy 26–29. Recently, Jurisic et al reported a patient affected from aggressive MEMP with a significant reduction in NK number and activity and a decrease in interleukin 2 production in cultured cells 27. In our case the analysis of lymphocyte phenotype showed depressed levels of NK too; however, no problems could be related to a decreased NK activity and in the next year the patient responded well to therapy.…”
Section: Discussionsupporting
confidence: 48%
“…Also, the degree of NK impairment was correlated with the clinical severity of the disease and the response to therapy 26–29. Recently, Jurisic et al reported a patient affected from aggressive MEMP with a significant reduction in NK number and activity and a decrease in interleukin 2 production in cultured cells 27. In our case the analysis of lymphocyte phenotype showed depressed levels of NK too; however, no problems could be related to a decreased NK activity and in the next year the patient responded well to therapy.…”
Section: Discussionsupporting
confidence: 48%
“…This could be due to the fact that the majority (80%) of NK/T‐cell lymphomas originate from the natural killer cell, whereas a small proportion is derived from the cytotoxic T cell and does not express CD56 . The extreme alterations in NK‐cell activity in aggressive form of lymphoma may also result in negativity of the CD56 …”
Section: Discussionmentioning
confidence: 99%
“…If positive, a whitish precipitate is noticeable in 24 hours in the case of Type I cryoglobulinemia as compared with Type II cryoglobulinemia where precipitation takes almost seven days . The precipitate redissolves on re‐warming at 37 °C . Immunofixation can be done to characterize the components of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…This type is mainly associated with lymphoproliferative disorders, such as multiple myeloma (MM), monoclonal gammopathy of unknown significance (MGUS), Waldenström's macroglobulinemia, lymphoma, and chronic lymphocytic leukemia . These monoclonal gammopathies are characterized by clonal proliferation of plasma cells that produce a monoclonal immunoglobulin protein . In MM, there is a proliferation of malignant plasma cells with deposition of proteins (monoclonal immunoglobulins) in blood vessels leading to vascular occlusion.…”
Section: Introductionmentioning
confidence: 99%